2021
DOI: 10.2174/1389201021666201008164056
|View full text |Cite
|
Sign up to set email alerts
|

Promising Anti-cancer Therapeutics From Mushrooms: Current Findings and Future Perceptions

Abstract: Background: Nowadays medicines derived from natural sources have drawn much attention as potential therapeutic agents in the suppression and treatment of cancer because of their low toxicity and fewer side effects. Objective: The present review aims to assess the currently available knowledge on the ethnomedicinal uses and pharmacological activities of bioactive compounds obtained from medicinal mushrooms towards cancer treatment. Methods: Literature search has been conducted for the collection of resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 186 publications
0
3
0
Order By: Relevance
“…Specifically, several epidemiological studies indicated that mushroom intake can protect against cancer, in particular, gastrointestinal and breast cancer. Furthermore, mushrooms have been used as therapeutic agents for different types of cancer, including breast cancer [ 31 , 58 , 153 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, several epidemiological studies indicated that mushroom intake can protect against cancer, in particular, gastrointestinal and breast cancer. Furthermore, mushrooms have been used as therapeutic agents for different types of cancer, including breast cancer [ 31 , 58 , 153 ].…”
Section: Discussionmentioning
confidence: 99%
“…Later on, edible mushrooms got popular due to their health benefits (Baruah, 1998;Chatterjee, 2017;Li, 2021). Other studies were also undertaken on glucans from mushrooms (Roy, 2009;Ojha, 2010;Sen, 2013), anticancer therapeutics (Panda, 2021), lignocellulosic degradation of the spent mushroom substrate (Devi, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that structural complexity of polysaccharides contributes to its bioactive potential. Medicinal mushrooms have demonstrated anti-proliferative effects from multiple studies Blagodatski et al, 2018;Shnyreva, Shnyreva, Espinoza, Padrón, & Trigos, 2018;Panda et al, 2020;Souilem et al, 2017;.…”
Section: Introductionmentioning
confidence: 99%